DESCRIPTION OF PAIN IN DIABETES MELLITUS AND NON-DIABETES MELLITUS PATIENTS AT PUSKESMAS DANUREJAN 1, YOGYAKARTA - Anandora Bagas Satrio Wibowo; Lisa Kurnia Sari; MMA Dewi Lestari; dr. Probosuseno Sp.PD; Yanti Ivana Suryanto (Berkala Ilmiah Kedokteran Duta Wacana, 2023)
Background Diabetes mellitus (DM) is a disease caused by impaired glucose metabolism, failure of the pancreas to produce the insulin hormone or the body's inability to respond to the insulin hormone. The neurologic complications are neuropathic or nociceptive pain. Neuropathic pain can cause the decrease in patient's quality of life. Knowing the spread of neuropathic pain based on anatomical predilection may help clinicians conduct early diagnosis and improve the patient's quality of life. Objective This study aim to determine the characteristics, prevalence and location of pain in patients with type 2 diabetes mellitus and non-diabetes mellitus at Puskesmas Danurejan I Yogyakarta. Methods A descriptive quantitative study on 42 secondary data from previous study in Puskesmas Danurejan I. The inclusion criteria were data of patients with neuropathic pain (electric shock-like pain, stabbing pain) and nociceptive pain  (burning sensation pain) who were > 40 years old. The exclusion criteria were incomplete data and recorded consumed non-steroidal anti-inflammatory drugs in the last of 4 days in previous study. Univariate and bivariate analysis were used in this study. Results Patients with DM accounted for 50% of cases by 21 people. Patients with DM had the most frequent comorbidities, such as hypertension (42.8%) and obesity (42.8%), Most patients with DM reported pain (85.7%) with neuropathic back pain (27.7%). Based on the type of pain, patients with DM most frequently reported neuropathic pain (66.7%) (p=0.001). Conclusion There was a relationship between diabetes mellitus and the incidence of neuropathic pain but not nociceptive pain. Keywords: diabetes mellitus; nociceptive pain; neuropathic pain.